2014
DOI: 10.1097/cji.0000000000000030
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Tumor Ascites CD14+ Cells Suppress Dendritic Cell–activated CD4+ T-cell Responses Through IL-10 Secretion and Indoleamine 2,3-Dioxygenase

Abstract: The observation that Th17 infiltration in ovarian cancer correlates with markedly improved survival has prompted the question of whether ovarian tumor antigen-specific Th17 responses to could be stimulated by tumor vaccination. Dendritic cells treated with IL-15 and an inhibitor of p38 MAPK signaling (DCIL-15/p38inhib) bias T cell responses toward a Th1/Th17 phenotype, raising the prospect of therapeutic vaccination, but significant barriers remain. Tumor vaccines, including DC vaccination, usually stimulate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…[9][10][11][12][13][14] For many of these tumors, elevated intratumoral CCL22 concentrations are associated with a higher tumor infiltration by Treg. Treg are an inhibitory subset of T helper cells, whose function is to suppress cytotoxic T effector cell functions, [15][16][17] involving cell-contact dependent and cell-contact independent mechanisms such as consumption of IL-2, expression of the cellsurface antigen CTLA-4 and secretion of inhibitory cytokines such as TGF-b and IL-10. [18][19][20][21] Treg have been found to accumulate in tumor tissues as well as in tumor-draining lymph nodes, malignant ascites and peripheral blood of tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] For many of these tumors, elevated intratumoral CCL22 concentrations are associated with a higher tumor infiltration by Treg. Treg are an inhibitory subset of T helper cells, whose function is to suppress cytotoxic T effector cell functions, [15][16][17] involving cell-contact dependent and cell-contact independent mechanisms such as consumption of IL-2, expression of the cellsurface antigen CTLA-4 and secretion of inhibitory cytokines such as TGF-b and IL-10. [18][19][20][21] Treg have been found to accumulate in tumor tissues as well as in tumor-draining lymph nodes, malignant ascites and peripheral blood of tumor patients.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of immunosuppressive factors produced within the tumor microenvironment, and the ability to target these factors could enhance anti-tumor immune responses. Several studies have focused on tumor-associated immune suppression mediated by T regulatory (Treg) cells, myeloid derived suppressor cells (MDSC), immunosuppressive dendritic cells, immune-inhibitory receptors, and inhibitory factors, including TGF-β, prostaglandins, and adenosine (12-17). In addition, components of ovarian ascites fluid have also been shown to inhibit immune function (18).…”
Section: Introductionmentioning
confidence: 99%
“… 36 The ability of CD14 + myeloid cells to produce IL-10 has a suppressive effect on T cells present in the OC tumor environment in the peritoneal cavity. 37 , 38 MYXV preferentially binds and enters human CD14 + cells rather than other immune cells to initiate early gene expression without resulting in a productive infection. 29 We found that MYXV did not affect the general viability of healthy human CD14 + cells.…”
Section: Discussionmentioning
confidence: 99%
“…OC tumor-associated CD14 + monocytes were purified from patient ascites as described previously. 38 Briefly, primary ovarian tumor ascites CD14 + cells were separated magnetically using commercially available columns and anti-CD14 conjugated microbeads (Miltenyi Biotec, Auburn, CA), according to the manufacturer’s instructions. The purity of recovered ascites CD14 + cells was typically 95%–98%.…”
Section: Methodsmentioning
confidence: 99%